Epidemiology of paediatric surgical admissions to a government referral hospital in the Gambia - Stephen W. Bickler; Boto Sanno-Duanda (The World Health Organization, 2000)
INTRODUCTION: There is a paucity of published data on the type of conditions that require surgery among children in sub-Saharan Africa. Such information is necessary for assessing the impact of such conditions on child health and for setting priorities to improve paediatric surgical care. METHODS: Described in the article is a 29-month prospective study of all children aged <15 years who were admitted to a government referral hospital in the Gambia from January 1996 to May 1998. RESULTS: A total of 1726 children were admitted with surgical problems. Surgical patients accounted for 11.3% of paediatric admissions and 34 625 total inpatient days. The most common admission diagnoses were injuries (46.9%), congenital anomalies (24.3%), and infections requiring surgery (14.5%). The diagnoses that accounted for the greatest number of inpatient days were burns (18.8%), osteomyelitis (15.4%), fractures (12.7%), soft tissue injuries (3.9%), and head injuries (3.4%). Gambian children were rarely admitted for appendicitis and never admitted for hypertrophic pyloric stenosis. The leading causes of surgical deaths were burns, congenital anomalies, and injuries other than burns. DISCUSSION: Prevention of childhood injuries and better trauma management, especially at the primary and secondary health care levels, should be the priorities for improving paediatric surgical care in sub-Saharan Africa. Surgical care of children should be considered an essential component of child health programmes in developing countries.